2006
DOI: 10.1007/s11135-006-9029-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban Households’ Cooking Oil and Fat Consumption Patterns in Turkey: Quality Vs. Quantity

Abstract: cooking oil, fats, olive oil, consumption, quality adjusted price, AIDS model, Turkey,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…The 5% of people that did not fry food in the online survey presented herein is similar with the 6% found by Doxa Market Research 26 and also the 8% by Statista 20 although Akbay 21 found it could be as high as 13.7%. Furthermore, irrespective of the debate on whether olive oil is suitable for frying, or whether it is considered to a speciality product as suggested by Martinez et al, 25 the online survey follows the tendencies noted by Wang et al 36 at least in terms of shallow frying/sautéing.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The 5% of people that did not fry food in the online survey presented herein is similar with the 6% found by Doxa Market Research 26 and also the 8% by Statista 20 although Akbay 21 found it could be as high as 13.7%. Furthermore, irrespective of the debate on whether olive oil is suitable for frying, or whether it is considered to a speciality product as suggested by Martinez et al, 25 the online survey follows the tendencies noted by Wang et al 36 at least in terms of shallow frying/sautéing.…”
Section: Discussionsupporting
confidence: 87%
“…In the paper by Akbay, 21 a survey of cooking oil and fat consumption patterns in Turkey has been carried out in which the author noted that the local dietary habits have been changing to a more Westernised life style. In the survey of 18,278 households, 86.3% purchased cooking oil and fat while the other 13.7% did not.…”
Section: Previous Studiesmentioning
confidence: 99%
“…When the benefits of olive oil are examined; it is known to be effective in the prevention of cardiovascular, hypertension, cancer, digestive system and nervous system diseases and has cell retention and aging retarding effects [22,23]. Up to now a lot of survey studies have been conducted about edible vegetable oils, olive oil, animal fat consumption habits and buying attitudes of individuals [4,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, to the best of our knowledge, no study has been carried out to examine consumers awareness about the effects of edible vegetable and animal fats on human health.…”
Section: Nov Tech Nutri Food Scimentioning
confidence: 99%
“…Tüketicilerin zeytinyağı talebi ve bunu etkileyen faktörlere yönelik literatürde birçok çalışma bulunmaktadır (Lazaridis, 2004;Tiryaki ve Akbay, 2005;Akbay, 2007;Tiryaki, 2008 ;Tunalıoğlu ve ark., 2012;Bernabéu and Díaz, 2016 ;Capogna and Gomez, 2016;Cömert, Adıyaman ve Özkaya, 2012;Erbaş ve Artukoğlu,2016). Bu çalışmalarda genellikle hane halkı bütçe verileri başta olmak üzere, tüketicilerin özelliklerine göre oluşturulan gruplar bazında zeytinyağı tercihleri ve etkili faktörler incelenmeye çalışılmıştır.…”
Section: Introductionunclassified